The development and evaluation of a social bookmarking service prototype for the University of the Philippines Diliman School of Library and Information Studies - Azul, Jason James R. (2011)
Web 2.0 is a web computing concept that emphasizes the use of the World Wide Web as a platform for giving users full control of content creation and manipulation. Libraries have been using Web 2.0 to reach out to clients, to promote the library and to collect and organize online resources. The UP Diliman Library System uses Web 2.0 technology in the form of blogs, social networking sites and instant messengers for reaching out to clients, for giving online reference services, and for promoting the library and its collection. Under the UP Diliman Library System, The UP School of Library and Information Studies Library use Web 2.0 technology in the form of a social networking site account. This was primarily used as a promotional aid and a place for making inquiries about the library.